Vegetation analysis in Cipayung City Forest, East Jakarta may reveal the difficulty of natural reproduction based on age pyramid - Vivit Nurholifah; Handayani (Bioma, 2024)
Urban forest is an important urban feature with various services for human and non-human urban populations. We surveyed three age-size groupings in Cipayung City Forest in East Jakarta using nested quadrats. This urban forest harbours 7 species of sapling, pole and tree. As the highest number of species is in tree grouping, lower in pole, lowest in sapling; in the form of upside-down/constrictive age pyramid, plant species in Cipayung City Forest may need management plant replanting to maintain its biodiversity. The highest IV is Eucalyptus globulus, which may not be able to reproduce naturally in Cipayung. The highest IV in pole grouping is C. inophyllum with a very healthy population in every age-size grouping. The highest IV in sapling grouping is C. fruticosa, an ornamental species.